Impact of COVID- 19 and Social Distancing on Mental Health - Kajal Gandhi; Kumar Gaurav Chhabra; Revati More; Ankita Rathi; Gargi Nimbulkar; Amit Reche (International Journal of Research in Pharmaceutical Sciences, 2020)
The Coronavirus Disease 2019 started in Wuhan Province, China and which spread to half a dozen countries between 2019 and 2020 and was declared a pandemic. This resulted in the implementation of a lockdown in different parts of the world, explaining it was an effective and essential way to break the cycle of infection. Physical distancing is the most important measure to break this infection cycle which affected many people's lives in different aspects. Mental health is considered to be one of the important components of the overall health as the definition given by the World Health Organization. It says that the person should be well-adjusted with the environment and should not be easily upset. He should know his needs, problems and goals properly; moreover, if he faces problems, he tries to solve them intelligently for which he tries to cope up with stress and anxiety. Along with all these things, he has good self-control balances between rationality and emotionality. It has likewise set off a wide variety of mental issues, for example, anxiety, panic disorder and depression. Most of the studies have reported negative impacts, including anger, stress symptoms and confusion. Education and training on pandemic should be provided by the authorities and health care workers.